Транскордонне співробітництво України: поняття, види, форми - Колодяжна, В.; Kolodyazhna, V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено підходи до визначення поняття «транскордонне співробітництво (ТКС)», проаналізовано види та форми його реалізації в умовах європейської інтеграції України.The article is dedicated to the complex analysis of the concept definition «Cross-border cooperation» and features of the development of different forms and types of the Ukrainian collaboration. Cross-border cooperation (CBC) is considered as a development tool of border areas and as a contributing factor to the realization of integration aspirations of our state. The generalization of features of the cross-border cooperation development indicates that the most developed cooperation at this stage is within European regions on the border between Ukraine and the EU, and along the borders of the former Soviet republics. Among the positive achievements of this cooperation can be distinguished clearly defined subjects (territorial communities, their representative bodies, local executive authorities), public organizations, entities and individuals participating in the CBC). A negative point is the lack of financing of cross-border projects and programs.
Transboundary Cooperation of Ukraine: Concept, Types, Forms
Keywords: транскордонне співробітництво; інтеграція; глобалізація; єврорегіон; Україна; cross-border cooperation; integration; globalization; the Euroregion; Ukraine